2022
DOI: 10.3390/biomedicines11010007
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation in Patients Co-Infected with SARS-CoV2 and Clostridioides difficile

Abstract: Background: The COVID-19 pandemic has challenged the treatment of Clostridioides Difficile (CD)-infected patients given the increasing number of co-infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this context, fecal microbiota transplantation (FMT) shows promise in modulating the immune system’s function and alleviating the burdens associated with this condition. Methods: To achieve this goal, we performed a comparative, retrospective, single-center study on 86 patients (admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“… 76 Lastly, a retrospective study of 86 patients who had coinfection of CDI and COVID-19 demonstrated that in patients that received both antibiotics and FMT had decreased abdominal pain, decreased relapse rates of CDI, and decreased biomarkers of inflammation compared to those who only received antibiotics. 77 In the 46 patients who underwent FMT, no adverse events were reported. In these studies, the authors speculate that FMT may have contributed to modulation of the gut–lung axis which is implicated in the pathogenesis of COVID-19.…”
Section: Fmt During the Covid-19 Pandemicmentioning
confidence: 91%
“… 76 Lastly, a retrospective study of 86 patients who had coinfection of CDI and COVID-19 demonstrated that in patients that received both antibiotics and FMT had decreased abdominal pain, decreased relapse rates of CDI, and decreased biomarkers of inflammation compared to those who only received antibiotics. 77 In the 46 patients who underwent FMT, no adverse events were reported. In these studies, the authors speculate that FMT may have contributed to modulation of the gut–lung axis which is implicated in the pathogenesis of COVID-19.…”
Section: Fmt During the Covid-19 Pandemicmentioning
confidence: 91%
“…As vehicles, other diluents such as yogurt or milk, can also be used. Larger volumes of prepared solutions tend to yield better results [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Methods Of Fmtmentioning
confidence: 99%
“…Many studies and therapeutic treatments of FMT were halted by these requirements, although new algorithms for donor screening have been developed since then [ 43 , 52 , 53 ]. The end of the year 2022 brought a study that encourages transplantation in patients with CDI and COVID-19 co-infection, with proven beneficial effects such as reducing inflammation, and also the need for antibiotics [ 54 ]. Although at the moment according to European Society of Clinical Micro-biology and Infectious Diseases: 2021 update on the treatment guidance document for Clostridioides difficile infection in adults FMT is approved only for recurrent or refractory CDI [ 71 ], recent studies outline the benefits of this procedure in many other diseases or co-infection.…”
Section: Methods Of Fmtmentioning
confidence: 99%
See 2 more Smart Citations